Analysis of the Financial Condition West Java Provincial Government, Indonesia - sofik handoyo; Syaiful Anas; Ivan Yudianto (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2019)
The purpose of the study is to assess the financial condition of 18 districts and 9 municipals in West Java Province. Assessing the financial condition was based on a 10 (ten) point financial ratio model developed by Kenneth Brown. Data on financial ratios for the 2013-2016 period was obtained from audited financial reports published by the west java provincial supreme auditor. Analysis of financial ratios was based on descriptive statistics and conducting Independent t-Test analysis. Research results showed that both district and municipal governments in West Java Province have a good financial condition. However, the performance of financial condition score for district governments shows a downward trend. In general, there is significant difference in the financial condition of district governments and municipal governments. In general, municipal governments showed better financial condition than district governments.